Effectiveness of Filtration Methods (Coffee Grounds and Silica Sand) in Reducing Iron (Fe) Levels in Leachate Water: Literature Review - Syamsuddin S; Anwar Daud; Anwar Mallongi; Atjo Wahyu; Ridwan Amiruddin; Wahiduddin (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Open dumps cause leachate pollution so that the complex composition of leachate including organic and anotorganic chemical content gets more attention for processing. Coffee grounds and silica sand have the potential to become filter media in reducing Fe pollutants in leachate at final disposal sites (TPA) because of their efficiency in removing heavy metals. Methods: Potentially eligible studies were identified from Proquest, Wiley, Google scholar, and Elsavier databases over the last ten years. The search strategy consisted of terms (Filtration Method, Leachate, Silica Sand, and Coffee Grounds). Then data extraction was carried out based on the inclusion criteria and then entered into Mendeley. The selected articles aim to investigate/detect filtration methods in leachate water. Results:. Heavy metals have harmful effects on ecosystems and human health because they are biodegradable. Adsorption in the filtration method absorbs certain substances due to the attraction of atoms or molecules. Activated coffee grounds act as active carbon which adsorbs Fe levels. Silica sand has surface characteristics that can be used as a filtration medium. Findings from the articles reviewed indicate that coffee grounds and silica sand have the potential to be used as filter media to reduce Fe concentrations in leachate water. Conclusion: The filtration method using coffee grounds and silica sand shows effectiveness in reducing Fe levels in landfill leachate water.